An outbreak of community-associated methicilin-resistant Staphylococcus aureus infection in a boarding school in Hong Kong (China) - Wong Mui-ling; Poon Kwok-ming; Wan Yuen-kong; Chuang Shuk-kwan; Kwok Lai-key; Pak Sik-on (World Health Organization Regional Office for the Western Pacific, 2014)
Background: In November 2012, an outbreak of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) skin and soft tissue infections affecting students at a boarding school in Hong Kong (China) was detected. Methods: A case was defined as any student or staff notified with MRSA infection from 25 October 2012 to 5 July 2013 with the clinical isolate being of staphylococcal cassette chromosome mec type IV or V and positive for Panton-Valentine leukocidin gene. We conducted field investigations, advised on control measures and enhanced surveillance for skin and soft tissue infections at the school. Decolonization therapies were offered to all cases and contacts, and carrier screening was conducted. Results: There were five cases; two (40%) were hospitalized and three (60%) required surgical treatments. Initial screening comprised 240 students and 81 staff members. Overall, four cases (80%) plus eight other students (3.3%) were carriers, with eight of 12 (66.7%) from the same dormitory. All staff members screened negative. After intensified control measures, the number of students screened positive for CA-MRSA decreased from nine to one with no more cases identified in the school. Conclusion: Identification of carriers, decolonization therapy, monitoring of cases and contacts and strengthening of environmental and personal hygiene were control measures that helped contain this CA-MRSA outbreak in a boarding school in Hong Kong (China).